A survey on microorganisms and their sensitivity by E-Test inventilator-associated pneumonia at Toxicological-IntensiveCare Unit of Loghman-Hakim Hospital - Talaie, H.; Sabeti, S.; Mahdavinejad, A. (Acta Biomedica Atenei Parmensis, 2011)
Introduction: Ventilator associated pneumonia (VAP) is the most common nosocomial infection at ICUs, with high mortality and morbidity. The diagnostic method for VAP is based on the combination of clinical, radiological, and microbiological criteria. Lower respiratory tract culture results are useful to confirm the etiology of VAP and adjusted antibiotics. Endotracheal aspiration (EA) is the simplest noninvasive technique for performing lower respiratory tract culture, with high sensitivity and moderately high specificity. The aim of this survey was to evaluate the quantitative cultures of endotracheal aspirates in VAP patients and  the sensitivity patterns of microorganisms through E-test. Method: Among 582 ICU admitted patients who were under mechanical ventilation for more than 48 hours, 72 suspected patients of VAP were prospectively evaluated during a 10 month period. Evaluation of our ICU standards by APACHE III scoring, and GCS were carried out on the first day of admission in all patients. Quantitative cultures of EA were performed on all 72 patients. Antibiotic resistance pattern of isolated pathogens was defined by E-test. Results: VAP was confirmed in 46 out of 72 cases (50, 69.4% males and 22, 30.6% females - mean age was 33±12 years) through quantitative cultures of EA samples. The probable incidence of VAP was 7.9% (per ventilated patients ≥48 hours). The mean APACHE III score was 31.28±16. GCS in most of the patients was between 8 and 12. Staphylococcus aureus was the most frequently isolated organism (58.7%), with high sensitivity to Amikacin, Ciprofloxacin, and Teicoplanin (>92%); Pseudomonas aeruginosa was the second most frequent organism (17.4 percent); Acinetobacter isolates were potentially drug resistant, and only Amikacin was effective. Conclusion: Tracheal aspirates in combination with clinical findings show important roles in the management of VAP and decrease inappropriate antimicrobial therapy. S. aureus is the main agent leading to VAP in the TICU of the Loghman Hakim Hospital.